URGENSI MEMASUKAN KURIKULUM BENCANA DI SEMUA LEVEL PENDIDIKAN DI INDONESIA - Indra Kristian; Endang Try Setyasih (Jurnal Dialektika: Jurnal Ilmu Sosial, 2023)
The community becomes the main object when a disaster occurs, the community should have the ability to know the vulnerabilities that exist, so that they can become the main actors (subjects) in disaster risk reduction efforts so that losses can be minimized. The community is an element that has direct experience in the event of a disaster so the understanding possessed is necessary for disaster risk reduction. In the context of natural disaster management, community response to disasters is very important to understand. Education has become one of the effective means to reduce disaster risk by including subject matter on natural disasters as mandatory lessons for every student at all levels, especially in schools in disaster risk areas. Learning and teaching approaches used in addressing the Disaster Risk Reduction (DRR) curriculum tend to be generally limited in application.